2014
DOI: 10.1016/j.fob.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive enzymatic analysis of the amylolytic system in the digestive fluid of the sea hare, Aplysia kurodai: Unique properties of two α‐amylases and two α‐glucosidases

Abstract: HighlightsThe amylolytic system of the digestive fluid of sea hare (Aplysia kurodai) was studied.Two α-amylases and two α-glucosidases were purified from the digestive fluid.Sea hare efficiently digests sea lettuce to glucose by a combination of these enzymes.Starch in sea lettuce is a predominant glucose source for sea hare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Our findings on the optimal pH for the lobster α-amylase (pH 5.5) agree with values obtained before from crude extracts [ 11 ] and other invertebrate purified α-amylases [ 19 , 69 ], with the pH of gastric juice in different spiny lobsters (e.g., 6.4 to 5.8 [ 8 , 11 , 73 ]), and with a pH allowing of high enzyme stability. The strong reduction of α-amylase activity we observed below pH 4 was also found in P .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings on the optimal pH for the lobster α-amylase (pH 5.5) agree with values obtained before from crude extracts [ 11 ] and other invertebrate purified α-amylases [ 19 , 69 ], with the pH of gastric juice in different spiny lobsters (e.g., 6.4 to 5.8 [ 8 , 11 , 73 ]), and with a pH allowing of high enzyme stability. The strong reduction of α-amylase activity we observed below pH 4 was also found in P .…”
Section: Discussionsupporting
confidence: 90%
“…argus crude extracts [ 11 ] and in α-amylases from distant groups (e.g., human salivary α-amylase [ 74 ]), in agreement with high sequence and structure conservation. Also, the relationship between stability of the lobster α-amylase and temperature is consistent with those observed for other α-amylases [ 69 ]. In addition, using CNP-G3 as the substrate we demonstrated that the lobster α-amylase has lower K m (0.36 mM) than pancreatic and salivary human α-amylases (1.15 mM) [ 75 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The East-Asian marine gastropod, sea hare ( A . kurodai ) consumes seaweed as staple food [ 18 ] and, although we have clarified the cellulose [ 18 ] and starch digestion systems [ 19 ], its defense mechanisms against seaweed secondary metabolites remain unclear. A .…”
Section: Introductionmentioning
confidence: 99%
“…kurodai digestive fluid which was incubated with cellulose fiber (CF-11) or semi-crystalline starch used as control. SDS-PAGE analysis revealed 21-kDa and 80-kDa proteins bound to cellulose and starch, respectively ( Fig 1A ), which were identified as ß-1,4 endoglucanase (AkEG21) and α-amylase (ApAmy80) based on exact similarity of N-terminal amino acid sequences EQKCQPNSHGVRMYQ [ 22 ] and ASAYHDP [ 33 ], respectively. Although AkEG21 does not possess a CBD [ 23 ], the enzyme showed strong binding to CF-11, filter paper, Avicel and ß-1,3-glucan curdlan, but not to starch and chitin ( Fig 1B ), indicating that AkEG21 has specific affinity to ß-1, 4 and ß-1,3 glucans.…”
Section: Resultsmentioning
confidence: 99%